2010
DOI: 10.1038/ijo.2010.62
|View full text |Cite
|
Sign up to set email alerts
|

Placental FTO expression relates to fetal growth

Abstract: Objective: The fat mass and obesity-associated gene (FTO) participates in the control of postnatal weight gain. We assessed whether FTO is expressed in human placenta and whether such expression relates to prenatal weight gain and to the rs9939609 single nucleotide polymorphism (SNP) in FTO. Design and subjects: In a birth cohort study, placentas from women (n ¼ 147) with an uncomplicated, singleton, term pregnancy were weighed at delivery. Real-time PCR was used to study, in placental tissue, the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 31 publications
11
28
0
Order By: Relevance
“…The results indicate that genetic variations in FTO do not have a strong main eVect in the modulation of birth weight, which is consistent with GWAS that has P value >0.2 for rs9939609 (Frayling et al 2007). A recent study (Bassols et al 2010) has shown that FTO was highly expressed in the placenta, and was associated with increased birth weight. This inconsistent Wnding suggests that FTO eVects may depend on expressed tissue.…”
Section: Discussionsupporting
confidence: 70%
“…The results indicate that genetic variations in FTO do not have a strong main eVect in the modulation of birth weight, which is consistent with GWAS that has P value >0.2 for rs9939609 (Frayling et al 2007). A recent study (Bassols et al 2010) has shown that FTO was highly expressed in the placenta, and was associated with increased birth weight. This inconsistent Wnding suggests that FTO eVects may depend on expressed tissue.…”
Section: Discussionsupporting
confidence: 70%
“…Four of the five CpG loci associated with placental Mn are of crucial importance in central nervous system differentiation and development ( EMX2OS 43 , ATAD2B 44 and EN1 45 ) and, when expressed in the placenta, fetal growth ( FTO 46 ). Moreover, a well-characterized link exists between FTO and obesity 46 .…”
Section: 1 Discussionmentioning
confidence: 99%
“…Moreover, a well-characterized link exists between FTO and obesity 46 . EN1 is a homeobox gene 45 , underscoring its importance in development.…”
Section: 1 Discussionmentioning
confidence: 99%
“…As the correct fetal development is based on the DNA-methylation-based programming, in theory the FTO gene is a promising candidate gene for predisposition to spontaneous abortion. The potential role of FTO in fetal development is further supported by the finding that in humans, FTO is highly expressed in placenta and its expression appears to correlate with increased fetal weight and length (5).…”
Section: Sirmentioning
confidence: 92%